Nonlinear ultrasonic inspection of smart carbon fibre reinforced plastic composites with embedded piezoelectric lead zirconate titanate transducers for space applications. (December 2019) - Andreades, Christos; Malfense Fierro, Gian Piero; Meo, Michele; Ciampa, Francesco
Carbon fibre reinforced plastic composites used in spacecraft structures are susceptible to delamination, debonds and fibre cracking that may arise during manufacturing, assembly or in-service operations (e.g. caused by debris impacts in near-Earth orbital spaceflights). Therefore, in situ and real-time health monitoring is necessary to avoid time-consuming and unsafe visual inspections performed either on-ground or during extra vehicular activities. In this article, a recently created 'smart' carbon fibre reinforced plastic composite structure with embedded piezoelectric lead zirconate titanate transducers was used to detect multiple areas of artificial delamination and real impact damage of different size using nonlinear ultrasound. The electrical insulation of embedded piezoelectric lead zirconate titanate transducers was achieved by interlacing a dry layer of woven glass fibre fabric between the sensor and the carbon fibre reinforced plastic plies before curing. Damage detection was successfully demonstrated using both second harmonic generation and nonlinear modulation (sidebands) of the measured ultrasonic spectrum. The material nonlinear response at the second harmonic and sidebands frequencies was also measured with a laser Doppler vibrometer to validate the nonlinear ultrasonic tests and provide damage localisation. Experimental results revealed that the proposed configuration of embedded piezoelectric lead zirconate titanate transducers can be utilised for on-board ultrasonic inspection of spacecraft composite parts.